Sistem Kuesioner Evaluasi Layanan Perkuliahan dan Kegiatan Kampus STMIK Bandung Terintegrasi - Mina Ismu Rahayu; Revi Antika Sri Anggraeni; Rena Wijaya (LPPM STMIK Bandung, 2024)
STMIK Bandung previously used a Google Form-based questionnaire but needed a new system to make data management easier. After the questionnaire filling is completed, it will be managed by the SPMI (Internal Quality Assurance System) section of STMIK Bandung in coordination with Vice Chairman 1 for the implementation and recapitulation of data and calculating the results of the questionnaire with excel. Then the results of this recapitulation were conveyed by the Vice Chairman 1 of STMIK Bandung to the Head of Study Program, Lecturers, and Leaders to support the evaluation of lectures. Lecture evaluation requires data on lecturers, study programs, and courses, while activity evaluation is based on the list of activities provided. This research ensures the accuracy and objectivity of the questionnaire, implements the Likert Scale, optimizes the results of the questionnaire in excel format, and integrates Laravel PHP and API for the efficiency and objectivity of evaluation at STMIK Bandung. The questionnaire filling method uses the Likert Scale to measure user satisfaction. Student personal data is integrated with the API when logging in using SSO for lecture questionnaires while activity services do not require login for general users. The results of the questionnaire can be exported in excel format, covering lecturer performance, learning services, and campus activities. The integration of Laravel PHP and API is expected to improve the efficiency and objectivity of evaluation.